Time-varying volatility in Malaysian stock exchange: An empirical study using multiple-volatility-shift fractionally integrated model - CHEONG, C (ELSEVIER SCIENCE BV, 2008)
This article investigated the influences of structural breaks on the fractionally integrated time-varying volatility model in the Malaysian stock markets which included the Kuala Lumpur composite index and four major sectoral indices. A fractionally integrated time-varying volatility model combined with sudden changes is developed to study the possibility of structural change in the empirical data sets. Our empirical results showed substantial reduction in fractional differencing parameters after the inclusion of structural change during the Asian financial and currency crises. Moreover, the fractionally integrated model with sudden change in volatility performed better in the estimation and specification evaluations. (c) 2007 Elsevier B.V. All rights reserved.